(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Social entrepreneurship is a start-up and entrepreneurial strategy to addressing social, cultural, and environmental problems via financing and implementation. This term may be used to a broad variety of organizations of various sizes, purposes, and religious affiliations. In India and across the globe, the idea of growing social entrepreneurship has aided in serving society more meaningfully than ever before, as well as the complete expression of the entrepreneurial spirit. Although social entrepreneurship is not a new concept, its popularity has recently soared to new heights. This article provides a comprehensive examination of social entrepreneurship, covering its conceptual foundation and operations. This study report also addresses the many difficulties that social entrepreneurs encounter, as well as their recommendations for improving India’s overall social entrepreneurship / entrepreneurship scenario. More study article investigates the relationship between social and economic entrepreneurship, as well as describing social entrepreneurship. The article also looks at the concepts from the perspective of an entrepreneur, such as societal demands and technical advancements. Social entrepreneurship has grown in importance and scope in recent years, and this article addresses both areas. Finally, this study shows how social entrepreneurship may change or influence the social system and social fibers in India and other developed countries at the bottom of the pyramid.